Images of Delhi A Literary and Humanistic Geography of Post-independence India - Dhussa, Ramesh Chandra (Cham : Springer International Publishing : Imprint: Springer, 2023)
The main objective of this book is to analyze prominent literary images of Delhi in post-independence India. The author has probed into a number of eminent writings in Hindi, English and other languages. The author's methodology, a humanistic and phenomenological approach, allows exploration of experiential dimension of writers' and their characters in various genres of literature. An inquiry into perceptions and imagination in literature enriches the understanding of place, space, time, and seasons, the concerns central to geography. The Perceptions of the metropolis of Delhi interestingly vary between authors and their characters. The images of Delhi in plethora of literary works show a wide spectrum of colors. The images evoke feelings of reverence, love, adoration, dislike, indifference or neutrality. Experiences vary from places of beauty and grandeur to utterly ugly environments. Natives express different views and attitudes toward the city of Delhi from those of expatriate writers.
Humanistic study of urban images -- Delhi: Evolution of an urban region -- Images of Delhi in Indo-Anglian and Hindi literary works -- Delhi: As an idea -- Old Delhi (Shahjehanabad) and adjacent regions -- New Delhi and neighboring colonies -- Four authors and their perceptions of Delhi -- Epilogue.
Keywords: Geography; Geography; Regional Geography